2007
DOI: 10.1055/s-2007-967941
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to the Enantioseparation of Betti Bases

Abstract: An improved method for enantioseparation of racemic 1-(a-aminobenzyl)-2-naphthols has been developed by the reaction in situ of Betti base product mixtures with L-(+)-tartaric acid taken in a 1:1 ratio. The products of this reaction are (-)-1-(a-aminobenzyl)-2-naphthol tartrate, the acetal of benzaldehyde and tartaric acid as well as (+)-1,3-diaryl-2,3-dihydro-1H-naphth[1,2-e][1,3]oxazine, which can be easily separated by crystallization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…[34] Compound 4 a is a polymorph of a previously reported structure (VEYSIC) with a P2 1 space group. [35] The conformations of both the structures are similar with a root-meansquare deviation of 0.3 . The molecular interactions are described in Table 3.…”
Section: Resultsmentioning
confidence: 84%
“…[34] Compound 4 a is a polymorph of a previously reported structure (VEYSIC) with a P2 1 space group. [35] The conformations of both the structures are similar with a root-meansquare deviation of 0.3 . The molecular interactions are described in Table 3.…”
Section: Resultsmentioning
confidence: 84%
“…[7] In the present work, we demonstrate the potential of these readily available Betti adducts as chiral inductors for the synthesis of enantiopure a-aminophosphonates.…”
mentioning
confidence: 72%
“…The products of this reaction were (S)-3a tartrate, the acetal of benzaldehyde and tartaric acid, and (þ)-2a, which were easily separated by crystallization (Scheme 1). 22 Harrison et al recently reported the syntheses of 6-bromosubstituted aminonaphthol derivatives (9aen) from 6-bromo-2-naphthol (7), methanolic ammonia and the corresponding aromatic aldehyde. The naphthoxazine intermediates 8aen were hydrolysed with hydrochloric acid to yield the desired aminonaphthol derivatives 9aen (Scheme 3).…”
Section: Syntheses With Ammonia As N Sourcementioning
confidence: 99%